2018
DOI: 10.3390/su10114301
|View full text |Cite
|
Sign up to set email alerts
|

Gated Neighborhoods, Privatized Amenities and Fragmented Society: Evidence from Residential Experience and Implications for Urban Planning

Abstract: Nowadays, urban space has become more fragmented and largely consists of many unconnected enclaves. The significance of neighborhood amenities to resident’s quality of life has been identified in the recent literature. However, studies have inadequately explored the real experience of residents in their use of neighborhood amenities under the gated urban form. Since the 1990s the urban environment of many Chinese cities has been re-shaped by the large creation of gated neighborhoods. Based on a case study in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Wang et al . (2018) noted that such housing preferences derive from an increasing role for private developers to provide such amenities, effectively taking over a responsibility that until recently was provided by municipal governments.…”
Section: Discussion and Conclusion: City Building Knowledge From Neig...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al . (2018) noted that such housing preferences derive from an increasing role for private developers to provide such amenities, effectively taking over a responsibility that until recently was provided by municipal governments.…”
Section: Discussion and Conclusion: City Building Knowledge From Neig...mentioning
confidence: 99%
“…Looking at Chinese urban development, Douglass et al (2012) termed this development as enclave urbanism which combines a housing type with a growing middle class preference. Wang et al (2018) noted that such housing preferences derive from an increasing role for private developers to provide such amenities, effectively taking over a responsibility that until recently was provided by municipal governments.…”
Section: Social Capital: Having a Sense Of Community Vs The Desire Fo...mentioning
confidence: 99%
“…She concluded that gated communities have several impacts on the surrounding neighbourhoods, such as access limitation and social inequality. From the spatial aspect, Wang et al [23] discussed the factors that motivate residents of the gated communities to open up with the surroundings. Their argument was based on a study carried out by the central government of China in 2016, which called for the suspension of developing gated communities and then gradually opening the existing gated communities.…”
Section: Social Spatial and Economic Impactmentioning
confidence: 99%
“…However, categorizing the population only through a single criterion is limited in guiding the reality, and the three groups obtained in this study integrated a variety of factors such as economy, education, age, and occupation, and this categorization made the image of the group closer to the reality and more precise. Residential compounds in China are closed, which means that some green space resources are privately owned [74]. Higher social status groups live in higher-quality compounds, which also means they enjoy higher-quality green space landscaping, resources that are not shared by disadvantaged groups.…”
Section: Green Space Preferences Across Diverse Social Groups Amidst ...mentioning
confidence: 99%